Smartness and Urban Resilience. A Model of Energy Saving - Gargiulo, Carmela; Zucaro, Floriana (TeMA - Journal of Land Use, Mobility and Environment, 2015)
Climate change, energy issues and urban population growth are among the main themes on which the scientific debate focuses today. Over the last decades, the literature has proposed different approaches to face these challenges. This paper focuses on two widely debated approaches: the smart and the resilient city paradigms, that continue to draw the attention of scholars and institutional bodies worldwide. The need to find strategies to reduce energy consumption and mitigate climate change impacts has been a prerequisite for the Smart Energy Master project for territorial governance of energy. One of the results is the Urban Saving Energy Model that "looks” at the several characteristics of a city in an integrated manner. This paper presents the results of a scientific and technical procedure that, starting from a thorough investigation of the physical and environmental characteristics of the city of Naples, has identified which variables have the greatest effect on energy consumption. The results have shown that the possibility of identifying an "ideal" sustainable urban form, able to maximize energy efficiency, still remains theoretical, opening up the possibility that there are different consumption patterns due to the different physical, environmental and building characteristics of urban areas.